Personality Predictors of Yips and Choking Susceptibility - Clarke, Philip; Sheffield, David; Akehurst, Sally (Frontiers in Psychology, 2020)
The ability to perform under heightened levels of pressures is one of the largest discriminators of those who achieve success in competition and those who do not. There are several phenomena associated with breakdowns in an athlete’s performance in a high-pressure environment, collectively known as paradoxical performances. The two most prevalent and researched forms of paradoxical performance are the yips and choking. The aim of the current study is to investigate a range of psychological traits (fear of negative evaluation, individual differences, anxiety sensitivity, self-consciousness, perfectionistic self-presentation and perfectionism) and their ability to predict susceptibility to choking and the yips in an experienced athlete sample. 155 athletes (Golfers n = 86; Archers n = 69) completed six trait measures and a self-report measure of yips or choking experience. The prevalence rate for choking and yips in both archers and golfers was 67.7% and 39.4% respectively. A 2 x 2 x 2 MANOVA and discriminant function analysis revealed that a combination of 11 variables correctly classified 71% of choking and non-choking participants. Furthermore, the ​analysis confirmed that a combination of four variables correctly classified 69% of the yips and non-yips affected participants. In this first study to examine both paradoxical performances simultaneously, these findings revealed that for the yips, all predictors stemmed from social sources (i.e. perfectionistic self-presentation), whereas choking was associated with anxiety and perfectionism, as well as social traits. This important distinction identified here should now be tested to understand the role of these traits as development or consequential factors of choking and the yips.